Interaction between the protective effects of cannabidiol and palmitoylethanolamide in experimental model of multiple sclerosis in C57BL/6 mice. (2nd April 2015) - Rahimi, A.; Faizi, M.; Talebi, F.; Noorbakhsh, F.; Kahrizi, F.; Naderi, N.
Highlights: We evaluated the protective effects of two non-psychoactive cannabinoids in the experimental allergic encephalomyelitis model. Both cannabidiol and palmitoylethanolamide per se ameliorated features of the experimental model of multiple sclerosis. There was an antagonistic interaction between cannabidiol and palmitoylethanolamide in protection against MOG-induced model. Abstract: Cannabinoids (CBs) have recently been approved to exert broad anti-inflammatory activities in experimental models of multiple sclerosis (MS). It has been demonstrated that these compounds could also have effects on neurodegeneration, demyelination, and autoimmune processes occurring in the pathology of MS. However, the clinical use of CBs is limited by their psychoactive effects. Among cannabinoid compounds, cannabidiol (CBD) and palmitoylethanolamide (PEA) have no psychotropic activities. We induced experimental autoimmune encephalomyelitis (EAE), a model of MS, by injecting myelin oligodendrocyte glycoprotein (MOG) to C57BL/6 mice. We assessed the effects of CBD, PEA, and co-administration of CBD and PEA on neurobehavioral scores, immune cell infiltration, demyelination, axonal injury, and the expression of inflammatory cytokines by using histochemistry methods and real-time RT-PCR. Treatment with either CBD (5 mg/kg) or PEA (5 mg/kg) during disease onset reduced the severity of the neurobehavioral scores of EAE. This effect of CBD and PEA was accompanied by diminished inflammation, demyelination, axonal damage and inflammatory cytokine expression while concurrent administration of CBD (5 mg/kg) and PEA (5 mg/kg) was not as effective as treatment with either drug per se. These results suggest that, CBD and PEA, non-psychoactive CBs, attenuate neurobehavioral deficits, histological damage, and inflammatory cytokine expression in MOG-immunized animals. However, there is an antagonistic interaction between CBD and PEA in protection against MOG-induced disease.